New Thrombolytic Infusion Application of Dissolving Renal Artery Embolic Thrombosis: Low-Dose Slow-Infusion Thrombolytic Therapy - Ahmet Karakurt (Case Reports in Nephrology)
Renal artery thromboembolism (RATE) is an uncommon complication of renal arteries from heart chamber. Although there is no treatment protocol prescribed with guidelines, thrombolytic agents such as rt-PA are frequently used. Unfortunately, current thrombolytic agent application protocol in treatment for the RATE is used in acute myocardial infarction or acute pulmonary embolism. In this protocol, 0.9–1.0% cerebral and 4–13% noncerebral hemorrhages are seen. In contrast to this protocol, we aimed to present a case of RATE, in which we applied low-dose, slow-infusion thrombolytic therapy, and we have not observed any complication such as cerebral and noncerebral hemorrhage.